Role of Metformin in Polycystic Ovary Syndrome - Nowak, Karolina; Nowak, Karolina; Olejarz, Zuzanna; Drygała, Zuzanna; Wyrwał, Julia; Zielińska, Zuzanna; Słowik, Magdalena; Nieć, Maria; Gierlach, Katarzyna; Krasuska, Martyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: PCOS is identified by the presence of underdeveloped follicles in the ovaries caused by a lack of ovulation, and it is linked to heightened production of androgens in the ovaries. The observable symptoms of PCOS encompass irregular or absent menstrual cycles, obesity, and indications of excess androgens such as acne or oily skin. Metformin could be advantageous for a specific group of women with PCOS. The aim of this study is to summarize the current knowledge regarding the effectiveness of metformin in the treatment of PCOS based on available scientific literature. A brief description of the state of knowledge: Metformin indirectly aids in enhancing ovulation and alleviating long-term metabolic issues, although its impact is considered moderate. Metformin also diminishes the levels of particular markers linked to arterial issues and chronic inflammation beneath the surface. This indicates a potential decrease in the continual risks of type 2 diabetes (DM) and cardiovascular disease (CVD) for women dealing with PCOS. Summary (conclusions): Managing PCOS involves personalized targets due to its diverse nature. In clinical practice, metformin is a recommended first step for managing PCOS in overweight or obese patients, particularly when oral contraceptives are not suitable or insulin resistance is evident.